Why Reform Fails: The 'Politics of Policies' in Costa Rican Telecommunications Liberalization - Bert Hoffmann (German Institute of Global and Area Studies (GIGA), 2007)
As the 'Washington Consensus' reforms are losing momentum in Latin America, the Inter- American Development Bank (IDB) is calling for shifting the focus from the content of policy choices to the political process of their implementation. As this paper studies the paradigmatic case of telecommunications reform in Costa Rica it underscores the importance of these 'politics of policies'. The analysis finds, however, that the failure of repeated liberalization initiatives was not only due to policy-makers' errors in steering the project through 'the messy world of politics' (IDB); instead, as liberalization remained unpopular, policy content indeed mattered, and only the interaction of both explains the outcome. Particular attention is drawn to the political feed-back effects, as the failed reform, precisely because it had been backed by bi-partisan support, became a catalyst for the disintegration of the country's long-standing two-party system. – – In dem Maße, in dem die mit dem 'Washington Consensus' verbundenen Reformen in Lateinamerika ins Stocken geraten sind, plädiert die Inter-American Development Bank (IDB) für eine stärkere Berücksichtigung nicht nur der Politikinhalte (policies), sondern auch des politischen Prozesses von deren Umsetzung (politics). Die vorliegende Untersuchung zum paradigmatischen Fall der Reform des Telekommunikationssektors in Costa Rica unterstreicht die Bedeutung dieser 'politics of policies'. Sie zeigt allerdings auch, dass Ursache für das Scheiten wiederholter Liberalisierungsinitiativen nicht nur Fehler der Politiker sind, das Vorhaben durch 'die unordentliche Welt der politics' (IDB) zu steuern. Die breite gesellschaftliche Opposition gegen den Liberalisierungskurs bleibt. Nur die Interaktion von beiden, politics und policies, erklärt Verlauf und Ergebnis der Reform. Besonderes Augenmerk widmet die Studie den politischen Rückwirkungen der gescheiterten Reform: Sie wurde, just weil sie von beiden etablierten Parteien unterstützt wurde, zum Katalysator für den Zerfall des seit Jahrzehnten etablierten Zweiparteiensystems des Landes.
Keywords: E61; E65; H42; L33; L96; O54; 330; liberalization; privatization; telecommunications; public enterprises; Costa Rica; development model; Inter-American Development Bank; Telekommunikation; IT-Industrie; Deregulierung; Costa Rica